STUDI KOMPARASI METODE A BA TA TSA DAN IQRA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN (PENELITIAN DI SDIT AL FITRAH RANCASARI BANDUNG) - Riza Pratama; Wati Karmila (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2020)
The purpose of this study is to find out how to compare the abilityto read the Qur'an using the A Ba Ta Tsa and Iqra methods of students inSDIT Al Fitrah, Manjahlega Village, Rancasari District, Bandung City.This study uses a quantitative approach and in the collection of data usedobservation and test methods. The data analysis technique iscomparative data analysis with t-test testing using the Separated Varianformula that compares the ability to read the Qur'an by using the Iqraand A Ba Ta Tsa methods for students. The results of data analysisshowed that the t count was 0.95. With a significant level ἀ = 0.05 due tothe two-tailed test, the value of ἀ / 2 = 0.05 / 2 = 0.025. then look for atable in the t-distribution table with the provisions: db = n-2, db = 34-2= 32 so t (ἀ, db) = t (0.025, 32) = 2,042. In this case, the provisionsapply that if -table "tcount "table (-2.042 <0.95 <2.042), then Ho isaccepted and Ha is rejected, which means that there is no significantdifference between the ability to read the Qur'an using the Iqra 'methodand A Ba Ta Tsa to students at SDIT Al Fitrah Manjahlega Village,Rancasari District, Bandung City